Hubungan Literasi Kesehatan dengan Manajemen Perawatan Diri Pasien Diabetes Melitus di Pelayanan Primer Kota Manado - Manariangkuba, Satri Maya; Nurmansyah, Muhamad; Wirawan , Alfonsius Ade (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2025)
Abstract Background: Diabetes mellitus is a chronic degenerative disease that cannot be cured, requiring long-term care and treatment. Having good health literacy enables diabetes mellitus patients to adopt appropriate health-related behaviors. Objective: To determine the relationship between health literacy and self-care management of type 2 diabetes mellitus patients in Primary Care Services in Manado City. Method: This study employed a quantitative research method with a correlational study design using a cross-sectional approach. The sample was selected using purposive sampling, consisting of patients who met the research criteria, resulting in a total of 112 participants. The research instruments included the Health Literacy Survey Europe 16 Questionnaire (HLS-EU-Q16) to assess health literacy levels and the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire to evaluate self-care management levels. Data analysis was performed using univariate analysis and bivariate analysis with the Gamma and Somers' test. Results: The study found p-value of 0.011 (p-value < 0.05) and an r-value of 0.939. Conclusion: There is a significant relationship between health literacy and self-care management of diabetes mellitus patients in Primary Care Services in Manado City, with a very strong positive correlation. Keywords: Health Literacy, Self-Care Management, Diabetes Mellitus